Causes and clinical picture of very early preterm birth - Mosendz, O.V. (Reproductive health of woman (Online), 2021)
The objective: the determination of the risk factors, causes and clinical features of very early preterm birth.Materials and methods. The data of anamnesis, the course of pregnancy, childbirth and perinatal outcomes in 166 women of reproductive age with very early preterm birth at 22–27 weeks of gestation were analyzed. The fact of childbirth at these terms of pregnancy is the main criterion of inclusion. The patients were divided into two groups depending on the criteria of live birth: 1 group — 79 women, whose labor was regarded as late miscarriage (retrospective study); 2 group — 87 women with very early preterm (prospective study). Exclusion criteria: congenital malformations of the fetus. Results. The main risk factors for the development of very early preterm labor are urogenital infections (83.7 % and 78.9 % in 1 and 2 groups, respectively). A combination of pathogens was found in almost half of the subjects (43 % in 1 group, 44 % in 2 group). The patients in both groups had a complicated general and obstetric anamnesis, in particular, a significant frequency of inflammatory processes of the genital organs (50.0 % – in 1 group and 59.2 % – in 2 group), surgical interventions (50.0 % and 59.2 %, respectively), as well as hormonal disorders and related diseases (ovarian dysfunction – 27.8 % and 27.6 %, uterine fibroids – 16.4 % and 17. 2%, ovarian cysts – 11.4 % in both groups). 35.4 % of patients in 1 group and 28.7 % of patients in 2 group had a history of chronic foci of infections, pathology of the urinary system – 30.3 % and 28.7 %, respectively, of the digestive tract – 24 % and 22.98 %, hypertension – 32.9 % and 31 %. The main complications of gestation in pregnant women in both groups in the II trimester were the threat of abortion (43 % and 30 %, respectively) and dysfunction of the fetoplacental complex (22.7 % and 21.8 %). This caused fetal growth retardation in both groups – 66 % and 63 % of newborns, respectively.Conclusions. Analysis of the general and obstetric history, the presence of infectious factor in combination with extragenital pathology confirm the polyetiology of the causes that leads to very early preterm birth. Considering the main risk factors of preterm birth, a complete examination for urogenital infections in women before and during pregnancy, followed by treatment and restoration of normal vaginal biocenosis, as well as the study of fetoplacental system function from early pregnancy is neseccary.Preventive measures and timely treatment of fetoplacental disorders should prolong pregnancy for the terms in which there is the best way to improve perinatal outcomes. Мета дослідження: визначення факторів ризику, причин і клінічних особливостей дуже ранніх передчасних пологів.Матеріали та методи. У ході дослідження проаналізовано дані анамнезу, перебіг вагітності, пологів і перинатальні наслідки у 166 жінок репродуктивного віку з дуже ранніми передчасними пологами у термінах 22–27 тиж гестації. Факт пологів у цих термінах вагітності — основний критерій включення. Пацієнток розподілено на дві групи залежно від критеріїв живонародженості: 1-а група — 79 жінок, пологи у яких розцінювали як пізній викидень (ретроспективне дослідження); 2-а група — 87 жінок, у яких пологи відбулися як дуже ранні передчасні (проспективне дослідження). Критерії виключення: вроджені вади розвитку плода. Пацієнткам обох груп проводили комплексне обстеження із застосуванням клінічних, інструментальних і лабораторних методів дослідження.Результати. Основними факторами ризику розвитку дуже ранніх передчасних пологів виявились урогенітальні інфекції (83,7 % і 78,9 % у 1-й і 2-й групах відповідно). Майже у половини обстежуваних виявлено поєднання збудників (45 % — у 1-й групі, 44 % — у 2-й групі). Пацієнтки обох груп мали обтяжений загальний і акушерський анамнез, зокрема, значну частоту запальних процесів статевих органів (50,0 % — у 1-й групі та 59,2 % — у 2-й групі), оперативних втручань (50,0 % та 59,2 % відповідно), а також гормональних порушень і зумовлених ними захворювань (дисфункція яєчників — 27,8 % та 27,6 %, міома матки — 16,4 % та 17,2 %, кісти яєчників — по 11,4 % в обох групах). Хронічні вогнища інфекцій в анамнезі мали 35,4 % пацієнток 1-ї групи та 28,7 % — 2-ї групи, патологію сечовидільної системи — 30,3 % та 28,7 % відповідно, травного тракту — 24 % та 22,98 %, гіпертонічну хворобу — 32,9 % та 31 %. Основними ускладненнями гестації у вагітних обох груп у ІІ триместрі стали загроза переривання вагітності (43 % і 30 % відповідно) і дисфункція фетоплацентарного комплексу (22,7 % і 21,8 %). Це стало причиною затримки розвитку плода в обох групах обстежуваних — у 66 % і 63 % новонароджених відповідно.Заключення. Аналіз загального і акушерського анамнезу, наявність інфекційного фактора у поєднанні з екстрагенітальною патологією підтверджують поліетіологічність причин, які призводять до дуже ранніх передчасних пологів. Ураховуючи основні фактори ризику передчасного розродження, необхідні ретельне обстеження на урогенітальні інфекції жінок ще на етапі прегравідарної підготовки та під час вагітності з подальшим лікуванням і відновленням нормального біоценозу піхви, а також дослідження функції фетоплацентарної системи, починаючи з ранніх термінів вагітності. Профілактичні заходи і своєчасне лікування фетоплацентарних порушень сприятиме пролонгуванню вагітності до більших термінів гестації, що є оптимальним способом покращення перинатальних результатів.